The role of minimal pairs in teaching Arabic/Model: Binary ) s - z) (Field study for students of the second grade primary learning in the public schools of Damascus) - Faour, Monera; Aljaber, Neeven (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This paper aims to identify the role of small Binaries in teaching the Arabic language for pupils in the primary stage, the Binary ( s - z) in particular. It holds especial importance for the second grade students who formed the sample of this research. The search also aims to explore the relationship between the teaching of Arabic through small Binaries, how it is related to the primary level, and the relationship between the training on those small Binaries and raising the level of the learner proficiency, and finally to reduce the sound problems that any new learner of Arabic may face, especially the dilemma of confusing characters that are similar in the output. It also stresses the importance of handling sound problems through practicing small Binaries by second grade students, elementary school in Damascus. The research sample was (814) pupils, the sample was randomly selected and was subject to two tests which the researcher had applied on a primary sample and the tests were approved and confirmed as true and stable. The study results indicated: 1-Small Binaries plays a role in teaching Arabic for secondary school students. 2-Small Binaries ( s – z ) plays a role in teaching Arabic for pupils in the second grade, primary school. 3-Practicing Small Binaries plays a role in the treatment of sound problems. 4-There is a correlation between the starter level of pupils in the primary stage and the importance of treating sound problems.